Evaluation of Acute Oral Toxicity of a Phytogenic Essential Oil-Based Anti-Diarrhoeal and Gut Function Modulator - Karande, Vikas Vasant; Gagare, Vaishnavi Sanjay; Sunidhi; Kotagiri, Ravikanth; Ganguly, Bhaskar (International Journal of Livestock Research, 2021)
A study was undertaken to evaluate the acute oral toxicity potential of Liqbiotic™ (M/s Ayurvet Limited, India) according to OECD 423 guidelines. Liqbiotic™ is an anti-diarrhoeal and gut function modulator for poultry and pigs. Six (3 male and 3 female) Swiss albino mice were used for the study, where each animal served as its own control. The animals were observed for the manifestation of toxic effects and mortality following the oral administration of the limit dose of test substance @ 2000 mg/kg body weight. No toxic effects or mortalities were observed till 14 days and Liqbiotic™ was found to be safe for oral use.